MECP2 Mutation Interrupts Nucleolin–mTOR–P70S6K Signaling in Rett Syndrome Patients - Olson, Carl O.; Pejhan, Shervin; Kroft, Daniel; Sheikholeslami, Kimia; Fuss, David; Buist, Marjorie; Ali Sher, Annan; Del Bigio, Marc R.; Sztainberg, Yehezkel; Siu, Victoria Mok; Ang, Lee Cyn; Sabourin-Felix, Marianne; et al. (Frontiers in Genetics, 2018)
Rett Syndrome (RTT) is a severe and rare neurological disorder that is caused by mutations in the X-linked MECP2 (Methyl CpG Binding Protein 2) gene. MeCP2 protein is an important epigenetic factor in the brain and in neurons. In Mecp2-deficient neurons, nucleoli structures are compromised. Nucleoli are sites of active ribosomal RNA (rRNA) transcription and maturation, a process mainly controlled by nucleolin and mechanistic target of rapamycin (mTOR)-P70S6K signalling. Currently, it is unclear how nucleolin-rRNA-mTOR-P70S6K signalling from RTT cellular model systems translates into human RTT brain. Here, we studied the components of nucleolin-rRNA- mTOR-P70S6K signalling in the brain of RTT patients with common T158M and R255X mutations. Immunohistochemical examination of T158M brain showed disturbed nucleolin subcellular localization, which was absent in Mecp2-deficient homozygous male or heterozygote female mice, compared to wild type. We confirmed by Western blot analysis that nucleolin protein levels are altered in RTT brain, but not in Mecp2-deficient mice. Further, we studied the expression of rRNA transcripts in Mecp2-deficient mice and RTT patients, as downstream molecules that are controlled by nucleolin. By data mining of published ChIP-seq studies, we showed MeCP2-binding at the multi-copy rRNA genes in the mouse brain, suggesting that rRNA might be a direct MeCP2 target gene. Additionally, we observed compromised mTOR-P70S6K signalling in the human RTT brain, a molecular pathway that is upstream of rRNA-nucleolin molecular conduits. RTT patients showed significantly higher phosphorylation of active mTORC1 or mTORC2 complexes compared to age- and sex-matched controls. Correlational analysis of mTORC1/2-P70S6K signalling pathway identified multiple points of deviation from the control tissues that may result in abnormal ribosome biogenesis in RTT brain. To our knowledge, this is the first report of deregulated nucleolin-rRNA-mTOR-P70S6K signalling in the human RTT brain. Our results provide important insight towards understanding the molecular properties of human RTT brain.